MALDI imaging mass spectrometry in glomerulonephritis: feasibility study. Issue 6 (5th February 2014) - Mainini, Veronica; Pagni, Fabio; Ferrario, Franco; Pieruzzi, Federico; Grasso, Marco; Stella, Andrea; Cattoretti, Giorgio; Magni, Fulvio
<x xml:space="preserve">Abstract</x> Aims The in‐situ proteomics technology known as matrix‐assisted laser desorption/ionization imaging mass spectrometry (MALDI‐IMS) is a powerful technique that combines traditional histology and proteomics. Methods and results MALDI‐IMS was applied to routine diagnostic kidney biopsies in a small group of cases of membranous glomerulonephritis and minimal change disease. Molecular changes were observed not only in the tissue areas with pathological alterations, but also in morphologically normal‐looking tissue, highlighting the potential feasibility of using MALDI‐IMS as a tool in nephropathology. Conclusions This technology can be applied to any biopsy where a frozen section is obtained as part of the diagnostic process. Although we do not yet know the molecular identity of the differentially expressed proteins/peptides, they could represent powerful classifiers of nosological groups.